Stagnation or Revival? : Palestinian Economic Prospects - World Bank (Washington, DC, 2017)
This report begins by documenting the Palestinian Authority's (PA's) ongoing fiscal crisis that threatens its ability to provide basic services to the population. In 2011, the PA required about US$1.5 billion dollars in budget support, of which US$200 million to cover development expenses not funded directly by donors. However, it only received about US$814 million in budget support and US$169 million in development financing, for a total of US$983 million. Ultimately, the PA can only hope to achieve fiscal sustainability through a combination of sustained private sector growth and continued internal reforms. Robust private sector growth is necessary for the PA to generate the revenues needed to sustain service delivery. Yet the private sector remains stifled as a result of Israeli restrictions on access to natural resources and markets. The West Bank has experienced a slowdown in economic growth in 2011, combined with double-digit growth in Gaza. The recovery in Gaza can be attributed to a combination of aid inflows and easing of restrictions on entry of goods from Israel-though it is important to keep in mind that the average Gaza today is worse off than s/he was back in the late nineties. The recent growth in Gaza is also driven largely by a boom in the construction sector, and Gaza infrastructure exhibits such gaps and disrepair that major investments are necessary and would generate important employment as well as future growth. The slowdown in growth in the West Bank, on the other hand, is the result of falling donor support, uncertainty caused by the PA's fiscal crisis, and lack of significant new easing of restrictions by the Government of Israel (GoI).